2020
DOI: 10.1111/tbed.13737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella Frintrop isolated from dromedary camels ( Camelus dromedarius )

Abstract: Different studies have reported the prevalence and antibiotic resistance of Salmonella in dromedary camels and its role in camelid-associated salmonellosis in humans, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In 2020, the camel population was 3,552,527 worldwide, with C. dromedarius accounting for approximately 90% of all camels [1,4]. Although Africa contains the largest population of the one-humped dromedary, since 1989, the Canary Islands have been the only region that provides dromedary camels in the European Union [5]. In 2013, the population of camels in the Canary islands was just under 1300 [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, the camel population was 3,552,527 worldwide, with C. dromedarius accounting for approximately 90% of all camels [1,4]. Although Africa contains the largest population of the one-humped dromedary, since 1989, the Canary Islands have been the only region that provides dromedary camels in the European Union [5]. In 2013, the population of camels in the Canary islands was just under 1300 [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, camel-based tourism has become one of the main attractions in several countries which includes camel riding, trekking, excursions and picture taking [8]. These camel-human close interactive encounters may lead to the transmission of zoonotic agents [5]. Several studies have shown that camels are carriers of many important pathogens such as Salmonella, extended-spectrum beta-lactamase-producing Escherichia coli and Pseudomonas aeruginosa, Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation